2018
DOI: 10.3389/fcimb.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Tight Junctions Prevent Effective Campylobacter jejuni Invasion and Inflammatory Barrier Disruption Promoting Bacterial Invasion from Lateral Membrane in Polarized Intestinal Epithelial Cells

Abstract: Campylobacter jejuni invasion is closely related to C. jejuni pathogenicity. The intestinal epithelium contains polarized epithelial cells that form tight junctions (TJs) to provide a physical barrier against bacterial invasion. Previous studies indicated that C. jejuni invasion of non-polarized cells involves several cellular features, including lipid rafts. However, the dynamics of C. jejuni invasion of polarized epithelial cells are not fully understood. Here we investigated the interaction between C. jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…These findings suggested that probiotic B. subtilis LF11 played a role on preventing cytokine-mediated gastrointestinal diseases. Previous studies have shown that proinflammatory cytokines including TNF-α mediate tight junction disruption, which increases the pathogen’s invasion process in epithelial cells ( Hatayama et al., 2018 ). In addition, it was noticed that the exclusion activity was always stronger than competition activity, suggesting that the supplementation with B. subtilis LF11 in diets was an effective way to prevent the Salmonella infection in poultry farming.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that probiotic B. subtilis LF11 played a role on preventing cytokine-mediated gastrointestinal diseases. Previous studies have shown that proinflammatory cytokines including TNF-α mediate tight junction disruption, which increases the pathogen’s invasion process in epithelial cells ( Hatayama et al., 2018 ). In addition, it was noticed that the exclusion activity was always stronger than competition activity, suggesting that the supplementation with B. subtilis LF11 in diets was an effective way to prevent the Salmonella infection in poultry farming.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the subcellular localization of claudin-1 and claudin-2 and found that ETEC infection induces the cytoplasmic distribution of claudin-2, but not claudin-1. Claudin-1 are exclusively located in the junctional area of IPEC-J2 cells following infection with a variety of porcine ETEC strains and porcine epidemic diarrhea virus [40, 41], indicating the essential role of this TJ protein in preventing intestinal pathogens to enter the paracellular space and invade the host [42]. Claudin-2 has been shown to form a paracellular channel for small ions and water and its upregulation is linked to leaky epithelial barriers and diarrhea [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…In S. aureus, fnbA and fnbB single mutants show no significant reduction in adhesion to FN [46], but both FNBPs are required for severe disease in mice [56]. Compared with other known and putative C. jejuni adhesins, a distinguishing feature of the CadF and FlpA proteins is that they promote cellular invasion by binding to FN bound to α 5 β 1 integrins on the basolateral surface of a cell [57][58][59]. However, in the early 1990s, it was also reported that C. jejuni invasion, but not cell adherence, was significantly reduced in the presence of chloramphenicol, a selective inhibitor of bacterial protein synthesis [60].…”
Section: Discussionmentioning
confidence: 99%